Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12887-022-03282-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of community health worker's performance at home-based newborn assessment supported by mHealth in rural Bangladesh

Abstract: Background In low to middle-income countries where home births are common and neonatal postnatal care is limited, community health worker (CHW) home visits can extend the capability of health systems to reach vulnerable newborns in the postnatal period. CHW assessment of newborn danger signs supported by mHealth have the potential to improve the quality of danger sign assessments and reduce CHW training requirements. We aim to estimate the validity (sensitivity, specificity, positive and negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The hands-on training to assess newborns and mothers for danger signs and breastfeeding assessment included maintaining hand hygiene before examining the newborn, and examination of the newborn for ten danger signs adopted from the 2009 National Newborn Health Strategy [ 35 ] as described previously [ 31 , 36 40 ]. CHWs examined five babies under the supervision of a neonatologist and study physician and received feedback on their performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hands-on training to assess newborns and mothers for danger signs and breastfeeding assessment included maintaining hand hygiene before examining the newborn, and examination of the newborn for ten danger signs adopted from the 2009 National Newborn Health Strategy [ 35 ] as described previously [ 31 , 36 40 ]. CHWs examined five babies under the supervision of a neonatologist and study physician and received feedback on their performance.…”
Section: Methodsmentioning
confidence: 99%
“…On each day, the physician collected the list of the households the CHWs visited and conveniently picked households to repeat assessments. The study physician and field supervisors observed CHW assessments of danger signs and phototherapy administration and provided feedback as necessary [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This included the responsibilities of CHWs, pregnancy care and maternal danger signs, delivery planning and safe delivery preparations, essential newborn care, breastfeeding and management of breastfeeding problems, postpartum services and the responsibilities of CHWs, neonatal jaundice types and symptoms, neonatal jaundice risk and management, descriptions of equipment and materials associated with jaundice management, and the sick newborn referral system and its components. In the second phase, CHWs received training on general examination of the newborn infant, physical examination for neonatal jaundice and assessment of neonates and mothers for other danger signs, [ 18 ] neonatal hyperbilirubinemia signs and symptoms, screening with transcutaneous bilimeter and management using mHealth application, assessment of breastfeeding, and management of breastfeeding problems.…”
Section: Methodsmentioning
confidence: 99%
“…During visits, CHWs counselled mothers on pregnancy care, safe delivery, essential newborn care, early initiation of breastfeeding, sensitized the mothers about the signs and symptoms of hyperbilirubinemia, and the importance of testing and treatment to prevent mortality and morbidity. [27] Parents were educated to make a plan for how they would get to the hospital if needed for emergency newborn care and treatment.…”
Section: Home-based Education Of Mothersmentioning
confidence: 99%
“…[48,49] In our study, this was overcome prenatal sensitization, the use of a point-of-care instant diagnostic device (transcutaneous bilimeter), and having access to a study physician to answer parental questions. [27] The objective measurement from the transcutaneous bilimeter helped improve con dence from families that phototherapy was needed. [42] The refusal rate for home phototherapy was 8%, which was low compared to other CHW-led home-based curative treatment approaches where refusal rates of home care for very severe disease and possible very severe disease were 23% and 38%, respectively.…”
Section: Refusal or Discontinuation Of Home Phototherapymentioning
confidence: 99%